Solvent effects on the intramolecular hydrogen-bond and anti-oxidative properties of apigenin: A DFT approach. (June 2017) - Zheng, Yan-Zhen; Zhou, Yu; Liang, Qin; Chen, Da-Fu; Guo, Rui; Xiong, Cui-Ling; Xu, Xi-Jian; Zhang, Zhao-Nan; Huang, Zhi-Jian
Abstract: Density functional theory (DFT) calculations were applied to analyze the effect of various solvents (water, dimethyl sulfoxide (DMSO), acetonitrile, ethanol, pyridine, chloroform and carbon tetrachloride (CCl4 )) on the intramolecular hydrogen-bond and anti-oxidative properties and of apigenin molecule. The different polarities of the seven solvents adequately cover the range of possible environments and enable informative comparisons from the results of DFT calculations. The solvent effects were introduced by using Tomasi's polarized continuum model (PCM). With the increasing dielectric constant of the environment, the geometry of apigenin monomer is more planar and apigenin molecule is more stable. Medium strength intramolecular hydrogen-bond was found between H5 and O4 in the apigenin molecule. With the increasing dielectric constant of the environment, the strength of the intramolecular hydrogen-bond was enhanced. Besides, the O5–H5⋯O4 intramolecular hydrogen-bond in apigenin molecule is the closed-shell interaction and considered to possess a dominant character of the covalent interactions in different environments. Solvents induce significant changes in enthalpies of charged species of apigenin. Thus, the preferred thermodynamically mechanism of the anti-oxidative progress for apigenin can be altered by the solvents. For the anti-oxidative progress, hydrogen atom transfer (HAT) is the thermodynamically dominant mechanism in vacuum, CCl4 and chloroform phases, while sequential proton loss electron transfer (SPLET) is more favored in pyridine, ethanol, acetonitrile, DMSO and water phases. Highlights: The intramolecular HB in apigenin is closed-shell interaction and possess a dominant character of covalent interactions. HAT is dominant mechanism in vacuum, CCl4 and chloroform phases. SPLET is more favored in other phases.